Cover Feature: Phage‐Derived and Aberrant HaloTag Peptides Immobilized on Magnetic Microbeads for Amperometric Biosensing of Serum Autoantibodies and Alzheimer's Disease Diagnosis (Analysis & Sensing 4/2021). Issue 4 (8th October 2021) - Valverde, Alejandro; Montero‐Calle, Ana; Arévalo, Beatriz; San Segundo‐Acosta, Pablo; Serafín, Verónica; Alonso‐Navarro, Miren; Solís‐Fernández, Guillermo; Pingarrón, José M.; Campuzano, Susana; Barderas, Rodrigo
Abstract : The cover feature illustrates an electrochemical bioplatform with full diagnostic capability for Alzheimer's disease exploiting for the first time the use of six phage‐derived and frameshift aberrant HaloTag peptides as receptors immobilized on magnetic microbeads, which were captured on multiplexed disposable electrodes to perform amperometry detection of specific serum autoantibodies. Cover design by Eloy Povedano and Víctor Ruiz Valdepeñas‐Montiel. More information can be found in the Communication by Dr. R. Barderas, S. Campuzano, J. M. Pingarrón and co‐workers .